Batch sintering method for high performance silicon nitride ceramic substrates
By using high-purity boron nitride powder and crucible, combined with multi-layer coating and step-by-step vacuum control pressure sintering method, the material pollution and temperature unevenness of high-performance silicon nitride ceramic substrates are solved, and high-efficiency and low-cost mass production is achieved.
Patent Information
- Application Number
- JP2023543223
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2021-01-20
- Filing Date
- 2022-01-17
- Publication Date
- 2025-02-06
- Estimated Expiration
- 2042-01-17
AI Technical Summary
The batch sintering process of existing high-performance silicon nitride ceramic substrates has problems of material pollution, temperature unevenness and low production efficiency. Especially under high temperature conditions, carbon pollution caused by graphite heating elements and temperature differences during multi-layer sintering affect material performance and production efficiency.
High-purity boron nitride powder and crucible are adopted, and through multi-layer coating and step-by-step vacuum control, combined with nitrogen or hydrogen protection atmosphere, pressure sintering is carried out to ensure multi-layer sintering of silicon nitride ceramic substrates, avoid metal impurities and carbon pollution, and control temperature uniformity and improve production efficiency.
Mass production of high-performance silicon nitride ceramic substrates is realized, ensuring the thermal conductivity and breakdown field strength of the material, reducing production costs, and improving product consistency and production efficiency.
Smart Images

Figure 0007627769000001 
Figure 0007627769000002 
Figure 0007627769000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a batch sintering method for high performance silicon nitride ceramic substrates and relates to the field of ceramic materials fabrication. [Background technology]
[0002] In recent years, semiconductor devices have been rapidly developing toward higher power, higher frequency, and greater integration. The heat generated by the operation of semiconductor devices is a factor that can cause failures in semiconductor devices, and the thermal conductivity of insulating substrates is an important factor that affects the overall heat dissipation of semiconductor devices. In addition, in fields such as electric vehicles and high-speed railways, semiconductor devices are constantly exposed to complex mechanical environments, including shocks and vibrations, during use, which places strict demands on the mechanical reliability of the materials used.
[0003] High-performance silicon nitride (Si3N4) ceramics have excellent mechanical and thermal performance. Due to their excellent mechanical performance and potential for high thermal conductivity, silicon nitride ceramics are expected to make up for the shortcomings of existing substrate materials such as alumina and aluminum nitride, and have great market prospects for application to high-end semiconductor devices, especially high-power semiconductor device substrates.
[0004] The main sintering processes for silicon nitride ceramic materials include reaction sintering, hot press sintering, pressureless sintering and pressure sintering.
[0005] In reactive sintering of silicon nitride, high-purity Si powder (or a small amount of Si3N4 powder is added) is used as the main raw material. First, a nitriding process is carried out at 1300-1500°C to convert Si to Si3N4, and then the temperature is raised to 1750-1850°C to form dense Si3N4 ceramic. This process has a small shrinkage rate (5% or less), making it suitable for producing workpieces with complex shapes. However, there is a tendency for nitriding to be incomplete, leaving a small amount of free Si, resulting in relatively poor material properties.
[0006] Silicon nitride hot press sintering is carried out by using Si3N4 powder as the main raw material and adding a small amount of sintering aids (usually rare earth oxides and metal oxides) in a nitrogen protective atmosphere of 1 atm, through liquid phase sintering mechanism at 1750~1850℃, and simultaneously forming Si3N4 dense ceramic through mechanical pressure. The material produced by this process generally has relatively good performance, but since this process requires external mechanical pressure, it is only suitable for producing workpieces with simple shapes, and also requires subsequent machining, so the production efficiency is low and it is not suitable for batch production.
[0007] Pressureless sintering (or atmospheric sintering) of silicon nitride uses Si3N4 powder as the main raw material, and by adding an appropriate amount of sintering aid, dense Si3N4 ceramics are formed by liquid phase sintering mechanism at 1750~1850℃ in a nitrogen protective atmosphere of 1atm. This process has high production efficiency and is suitable for batch production, but Si3N4 powder is prone to decomposition reaction at high temperatures (about 1800℃ or higher), so the material performance is relatively low.
[0008] In the pressure sintering of silicon nitride, Si3N4 powder is used as the main raw material, and a suitable amount of sintering aid is added to form dense Si3N4 ceramics by liquid phase sintering mechanism at 1800-2000℃ in a nitrogen protective atmosphere with a certain pressure. This process is a preparation process developed to address the high temperature decomposition problem that exists in the pressureless sintering of silicon nitride, and the nitrogen pressure is generally 0.1-10MPa, and the sintering temperature can reach 1800-2000℃. This process solves the high temperature decomposition problem of Si3N4 through the inhibitory effect of the high pressure nitrogen atmosphere, further improves the sintering temperature, ensures the performance of the prepared material, and retains the characteristics of high production efficiency, and is applicable to batch production. It is recognized as the optimal process method for preparing high performance silicon nitride ceramic materials.
[0009] Although pressure sintering is the most promising and potential process method for batch production of high performance (high thermal conductivity, high strength, high breakdown field strength) silicon nitride ceramic substrate materials, it still has the following disadvantages: (1) There is a carbon-rich atmosphere in the sintering furnace, which is composed of a graphite heating element and a graphite heat shield, and the latter contaminates the substrate materials to different degrees, which deteriorates the insulating performance of the silicon nitride ceramic substrate and reduces the breakdown electric field strength. (2) The production sintering furnace generally has a large hearth space, and heat transfer is mainly by radiation under high temperature conditions of 1800-2000℃. The heating elements of the sintering furnace are generally arranged around the four sides of the hearth, and there will inevitably be a certain degree of deviation between the actual temperatures at different positions inside the hearth, which will affect the consistency of the material performance. In particular, in order to increase the product throughput, it is necessary to set up a multi-layer grill inside the hearth, which will inevitably worsen the temperature non-uniformity at different positions inside the hearth. [Prior art documents] [Patent documents]
[0010] [Patent Document 1] China Patent Application Publication No. 108495831 [Patent Document 2] China Patent Application Publication No. 109987944 [Patent Document 3] China Patent Application Publication No. 103781742 [Patent Document 4] JP 2011-178598 A [Patent Document 5] International Publication No. 2019 / 235593 Summary of the Invention
[0011] In response to the technical challenges of batch sintering high performance silicon nitride ceramic substrates, the inventors have developed a pressure sintering batch fabrication process that simplifies the design and control of multiple layer stacks of substrate blanks, the design and control of crucible and graphite furnace tooling, and Debinding By designing and controlling the sintering process, a batch sintering method for high performance silicon nitride ceramic substrates is finally provided. The batch sintering method for high performance silicon nitride ceramic substrates of the present invention includes: (1) stacking silicon nitride ceramic substrates in a boron nitride crucible and coating one layer of boron nitride powder between adjacent silicon nitride ceramic substrates; (2) gradually evacuating the crucible and then heating the crucible at 500-900°C in a nitrogen or reducing atmosphere; Debinding the step of evacuation in stages is at least a two-stage evacuation or at least a three-stage evacuation, and in the case of two-stage evacuation, the parameters of the step-by-stage evacuation are evacuation for 20-30 minutes, achieving a vacuum level of 20-30 kPa, and then evacuation for 10-20 minutes, and reducing the vacuum level to less than 10 Pa; or in the case of three-stage evacuation, the parameters of the step-by-stage evacuation are first evacuation for 10-15 minutes, achieving a vacuum level of 60-80 kPa, then evacuation for 10-15 minutes, achieving a vacuum level of 10-30 kPa, and finally evacuation for 10-15 minutes, and reducing the vacuum level to less than 10 Pa; and then pressure sintering at 1800-2000°C in a nitrogen atmosphere to realize batch production of high-performance silicon nitride ceramic substrates.
[0012] The present invention uses high-purity boron nitride powder and crucible to avoid the introduction of metal impurity ions and carbon atmosphere during the sintering process, which contributes to ensuring the thermal conductivity and breakdown electric field strength of the substrate material. The present invention further utilizes the characteristics of the chemical stability of boron nitride powder at high temperatures, and a layer of high-purity boron nitride powder is coated between the substrate raw materials to prevent adjacent substrates from adhering to each other, thereby realizing stacked batch sintering of multiple substrates and improving production efficiency. The present invention uses a step-by-step vacuuming measure to control the vacuuming speed and vacuum suction force, avoiding the displacement of boron nitride powder between the substrate raw layers, ensuring that the silicon nitride ceramic substrate is not formed to be adhered to each other during the sintering process, and heat-treating the substrate raw materials under a slightly positive pressure reducing atmosphere to avoid further oxidation of silicon nitride and boron nitride powder, ensuring the physical properties and surface mass of the silicon nitride ceramic substrate produced. The cooperation of the above-mentioned multiple technical measures improves production efficiency and reduces production costs on the premise of ensuring the performance of the silicon nitride ceramic substrate.
[0013] Preferably, the number of stacked silicon nitride ceramic substrate sheets is 5 to 50.
[0014] Preferably, the boron nitride powder has an O content of 1% or less, a C content of 0.01% or less, a metal impurity ion content of 0.02% or less, and an average particle size of the boron nitride powder of 1 μm to 5 μm, preferably 2 μm to 5 μm. The present invention avoids contamination of silicon nitride ceramic material by controlling the purity of the boron nitride powder (O content, C content, metal impurity ion content, etc.) and ensures performance such as thermal conductivity and breakdown field strength of the ceramic substrate. The present invention ensures the surface mass (flatness, roughness, etc.) of the produced silicon nitride ceramic substrate by mainly controlling the particle size of the boron nitride powder.
[0015] Preferably, the dosage of the boron nitride powder is 1.0 to 2.5 mg / cm. 2 and preferably 1.5 to 2.5 mg / cm 2 The present invention ensures uniform shrinkage and excellent isolation effect of silicon nitride ceramic substrate by controlling the coating amount of boron nitride powder per unit area of substrate base.
[0016] Preferably, in step (2), the pressure of the nitrogen atmosphere or reducing atmosphere is 0.05 to 0.2 MPa, preferably 0.1 to 0.2 MPa. This pressure range belongs to a slightly positive pressure and contributes to improving the pass rate, the reducing atmosphere is a mixed atmosphere of nitrogen / hydrogen with a hydrogen content of 5% or less, and the Debinding The duration is 1 to 3 hours.
[0017] Preferably, the nitrogen atmosphere pressure in the pressure sintering is 0.5 to 10 MPa, and the pressure sintering time is 4 to 12 hours.
[0018] Preferably, a plurality of boron nitride crucibles are uniformly arranged in a graphite furnace tool for pressure sintering. Preferably, the graphite furnace tool has a multi-layer grill structure. Furthermore, the present invention adopts a high heat capacity graphite furnace tool with a multi-layer grill structure to further average the internal temperature field of the sintering furnace, thereby ensuring the high performance consistency of batch pressure sintering of silicon nitride ceramic substrates.
[0019] Preferably, the silicon nitride ceramic substrate green body is produced by slurry tape casting or powder press molding. The slurry tape casting step includes the steps of (1) using at least one of silicon nitride powder and silica fume as raw material powder, mixing it with a sintering aid, a dispersant, an antifoaming agent, a binder and a plasticizer in a protective atmosphere, and then vacuum degassing to obtain a mixed slurry, (2) performing tape casting and drying in a nitrogen atmosphere to obtain a first green body, and (3) performing a shaping pretreatment on the obtained first green body to obtain a silicon nitride ceramic substrate green body. Preferably, when the raw material powder contains silica fume, the mass of silica fume is 75% or more of the mass of the raw material powder, and the mass of the raw material powder is the sum of the masses of silicon nitride generated after the silicon nitride powder and silica fume are completely nitrided. More preferably, before pressure sintering, Debinding The silicon nitride ceramic substrate is subjected to a nitriding treatment, and the parameters of the nitriding treatment are that the nitrogen atmosphere is a mixed nitrogen / hydrogen atmosphere with a hydrogen content of 5% or less, the pressure is 0.1 to 0.2 MPa, the nitriding temperature is 1350 to 1450°C, and the nitriding time is 3 to 6 hours.
[0020] Meanwhile, the present invention further provides a high-performance silicon nitride ceramic substrate prepared according to the above batch sintering method, the high-performance silicon nitride ceramic substrate having a pass rate of ≧60%, preferably a pass rate of ≧70%, more preferably a pass rate of ≧80%, and most preferably a pass rate of ≧90%. Effect of the Invention
[0021] One of the salient features of the present invention is that the use of high purity boron nitride powder and crucible avoids the introduction of impurity ions, which contributes to ensuring the thermal conductivity and breakdown field strength of the substrate. Another salient feature of the present invention is that the use of measures such as lamination method, kiln tool design, and vacuum process control realizes batch sintering of high performance silicon nitride ceramic substrates, improving production efficiency and reducing production costs. [Brief description of the drawings]
[0022] [Figure 1] FIG. 1 is a schematic diagram of the silicon nitride substrate. [Diagram 2] FIG. 1 is a schematic diagram of a silicon nitride substrate having a surface coated with boron nitride powder. [Diagram 3] FIG. 1 shows a schematic of the raw stack of 20 silicon nitride substrates with boron nitride powder coating on their surfaces. [Figure 4] FIG. 1 is a schematic diagram of 20 stacked silicon nitride substrates placed in a boron nitride crucible. [Diagram 5] FIG. 1 is a schematic diagram showing the orderly arrangement of a boron nitride crucible containing the silicon nitride substrate matrix to be sintered on a graphite kiln tool (single layer). [Figure 6] FIG. 1 is a schematic diagram of the orderly placement of a boron nitride crucible containing the bulk of a silicon nitride substrate to be sintered onto a graphite furnace tool (multilayer stacking). [Figure 7] FIG. 2 is an actual diagram of the silicon nitride ceramic substrate produced in Example 1. [Figure 8] Table 1 shows the performance parameters of the BN powders used in the examples and comparative examples of the present invention. [Figure 9] Table 2 shows the manufacturing process of the silicon nitride ceramic substrate of the present invention. [Figure 10] Table 3 shows the performance parameters of the silicon nitride ceramic substrate of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0023] The present invention will be further described below with reference to the following embodiments. It should be understood that the following embodiments are only for illustrating the present invention, and are not intended to limit the present invention.
[0024] In the present disclosure, a pressure sintering process is used to achieve batch sintering of high performance silicon nitride ceramic substrates, specifically, stacking design and control of multiple substrate blanks, crucible and kiln tooling design and control, and Debinding and sintering process design and control to achieve batch sintering of high performance silicon nitride ceramic substrates.
[0025] An exemplary batch sintering method for high performance silicon nitride ceramic substrates is described below.
[0026] Preparation of silicon nitride ceramic substrates Specifically, a silicon nitride ceramic substrate is produced through steps such as slurry preparation, vacuum degassing, tape casting, drying the substrate, and shaping the substrate during the tape casting process.
[0027] The present invention achieves the purpose of reducing or eliminating bubbles in the slurry or reducing agglomeration in the slurry by thorough ball mill mixing in a protective atmosphere during the tape casting slurry preparation process, combined with long-term degassing in low vacuum. During the tape casting molding process, the cylindrical scraper and its highly precise control, and the drying treatment measures of the cast film blanks with a continuous hot N2 atmosphere with temperature increments, realize the preparation of high-quality and defect-free cast films and precise control of their thickness uniformity. Measures such as ball mill mixing and N2 protective atmosphere during the tape casting molding process inhibit the secondary oxidation of silicon nitride powder raw material, ensuring that the prepared silicon nitride ceramic substrate has high thermal conductivity properties. The cold isostatic pressing pretreatment process further improves the density, thickness uniformity and flatness of the prepared cast film.
[0028] Creation of agglomeration-free, bubble-free slurry At least one of silicon nitride powder and silica fume is used as raw material powder, and is mixed with sintering aid, dispersant, defoamer, binder and plasticizer in a protective atmosphere (for example, N2 atmosphere, pressure may be 0.1MPa) by ball mill mixing, and then vacuum degassing is performed to prepare a non-aggregated and non-bubble mixed slurry. In the ball mill process, silicon nitride ceramic polishing balls are used, and anhydrous ethanol is used as the ball mill medium. Here, the sintering aid may be rare earth oxide and alkaline earth metal oxide, and the silicon nitride powder and / or silica fume are completely nitrided and formed, and the total mass of the silicon nitride and sintering aid is 4-5wt%. The rare earth oxide contains at least Y2O3. The alkaline earth metal oxide contains at least MgO. The molar ratio between the rare earth oxide and the alkaline earth metal oxide may be (1.0-1.4):(2.5-2.9). Here, when silica fume is contained, the content of the silica fume is 75 to 100 wt% of the total mass of silicon nitride powder and / or silicon nitride completely nitrided by silica fume. The prepared slurry is subjected to a vacuum bubble removal treatment, the degree of vacuum is -0.1 to -10 kPa, and the degassing time is 6 to 24 hours. The dispersant is selected from at least one of polyethylene glycol (PEG) and triethyl phosphate (TEP), and the amount added is 0.2 to 1.0 wt% of the total mass of silicon nitride powder, silicon nitride completely nitrided by silica fume, and sintering aid. The defoaming agent is oleic acid, and the amount added is 0.2 to 1.0 wt% of the total mass of silicon nitride powder, silicon nitride completely nitrided by silica fume, and sintering aid. The binder is polyvinyl butyral (PVB), and the amount added is 5 to 9 wt% of the total mass of silicon nitride powder, silicon nitride completely nitrided by silica fume, and sintering aid. The plasticizer is selected from at least one of diethyl phthalate (DEP), dibutyl phthalate (DBP) and polyethylene glycol (PEG), and the amount added is 2 to 6 wt % of the total mass of the silicon nitride powder, the silicon nitride formed by complete nitridation of silica fume, and the sintering aid.
[0029] Cast film fabric with uniform thickness and no bubbles on the surface Tape casting is performed in an N2 atmosphere (0.1-0.2 MPa). Drying is performed in a flowing hot N2 atmosphere (flow rate is 10-1000 liters / min) to produce a cast film fabric with uniform thickness and no bubbles on the surface. As an example, tape casting is performed in an N2 atmosphere using a cylindrical scraper taper, and the height of the scraper is controlled to adjust the thickness of the cast film fabric. The cast film fabric is dried using a flowing hot N2 atmosphere with increasing temperature, the temperature range of the hot N2 atmosphere is 40-85°C, and the pressure of the atmosphere is 0.1-0.2 MPa. For example, if there are two temperature stages, the temperature of the first stage is 40-65°C, the drying time is 15-30 minutes, the temperature range of the second stage is 60-85°C, the drying time is 15-30 minutes, and the temperature of the first stage is < the temperature of the second stage. For example, if there are three temperature stages, the first stage temperature is 40 to 60°C and the drying time is 5 to 20 minutes, the second stage temperature range is 55 to 70°C and the drying time is 5 to 20 minutes, the third stage temperature range is 65 to 85°C and the drying time is 5 to 20 minutes, and the first stage temperature<second stage temperature<third stage temperature.
[0030] Pre-shaping treatment of cast film fabric (first fabric) Under a constant pressure (40 to 200 MPa), the cut cast film raw material (substrate raw material) is subjected to a cold isostatic compression pretreatment to improve the thickness uniformity and flatness of the cast film, thereby obtaining a silicon nitride ceramic substrate raw material. Here, the shaping pretreatment time may be 2 to 10 minutes.
[0031] Preparation of deposition substrate fabric A certain number of silicon nitride ceramic substrates are stacked, and a layer of high-purity boron nitride powder is coated between the substrates to prevent adjacent substrates from adhering to each other. Here, the number of substrates stacked may be 5 to 50, and this range contributes to stacked sintering. If the number of substrates stacked is less than 5, production efficiency is affected. If the number of substrates stacked is more than 50, the conformity between the substrates is affected and adhesion is likely to occur between the lower substrates when the difference in the force receiving state between the upper and lower substrates is too large. Here, the high-purity boron nitride powder has an O content of 1% or less, a C content of 0.01% or less, and a metal impurity ion content of 0.02% or less. If the content of O, C, and metal impurity ions in the boron nitride powder is high, the performance of the substrate, such as thermal conductivity and breakdown electric field strength, is reduced. Here, the average particle size of the high purity may be 1 to 5 μm. If the average particle size of the boron nitride powder used is too small, adhesion phenomenon is likely to occur between the substrate and the boron nitride powder. Furthermore, a decrease in the particle size of the boron nitride powder, always accompanied by an increase in the O content, will cause a deterioration in the thermal conductivity and breakdown field strength of the substrate, and if the average particle size of the boron nitride powder used is too large, the flatness of the substrate will decrease and the surface roughness will increase. In an alternative embodiment, the boron nitride slurry is coated by screen printing, and the dosage of the boron nitride powder is 1.0-2.5 mg / cm. 2 If the amount of boron nitride powder used is too small, adhesion phenomenon is likely to occur between the prepared substrates, and if the amount of boron nitride powder used is too large, the high temperature shrinkage of the substrates is hindered to a certain extent, and the size of the substrates prepared under the same conditions is relatively large, the flatness is reduced, and the surface roughness is increased.
[0032] Batch board fabric Debinding The laminated substrate is placed in a high-purity boron nitride crucible and placed in a heat treatment furnace, and the vacuum is gradually drawn to avoid the displacement of the boron nitride powder between the layers. Then, the substrate is heat-treated ( DebindingIn an alternative embodiment, the speed of the stepwise evacuation is controlled by the vacuum valve opening, the evacuation time, and the vacuum level. Here, the stepwise evacuation can be divided into at least three stages, first, evacuation for 10-15 minutes to reach a vacuum level of 60-80 kPa, then evacuation for 10-15 minutes to reach a vacuum level of 10-30 kPa, and then evacuation for 10-15 minutes to reach a vacuum level of less than 5 Pa. Here, Debinding In the treatment, a slight positive pressure is generated in the mixed atmosphere by injecting reduced nitrogen with a hydrogen content of 5% or less. The atmospheric pressure may be 0.1-0.2 MPa, the treatment temperature may be 500-900°C, and the treatment time may be 1-3 h. If a stepwise evacuation is not adopted, the evacuation speed will be too fast and the vacuum suction force will be too large, making it difficult to completely avoid the displacement of the isolating boron nitride powder between the substrates, and most of the adjacent substrates will adhere to each other in the subsequent high-temperature sintering process.
[0033] Nitriding of batch substrate material When the raw powder contains silica fume, the substrate is subjected to nitriding treatment in a hydrogen / nitrogen mixed atmosphere with a hydrogen content of 5% or less at a certain temperature condition, where the atmospheric pressure may be 0.1-0.2 MPa, the nitriding temperature may be 1350-1450°C, and the nitriding time may be 3-6 hours.
[0034] Batch substrate dough sintering Under high nitrogen pressure, the temperature field inside the sintering furnace is further uniformed by using a high heat capacity graphite furnace tool, and pressure sintering is performed at a constant temperature to realize the densification of the batch substrate. Here, the parameters of pressure sintering under high nitrogen pressure may be the atmospheric pressure of 0.5-10 MPa, the sintering temperature of 1800-2000°C, and the heat retention time of 4-12 hours. Preferably, the high heat capacity graphite furnace tool has a multi-layer grill structure, and the boron nitride crucible with the substrate material attached is uniformly arranged in the graphite furnace tool.
[0035] The present invention achieves batch sintering of high-performance silicon nitride ceramic substrates. Using a laser thermal conductivity meter, the thermal conductivity of the resulting silicon nitride ceramic substrate material was measured to be 80 W m -1 ·K -1 It was measured that the breakdown electric field strength of the obtained silicon nitride ceramic substrate material is greater than 25KV / mm using a breakdown voltage strength tester. It was measured that the thickness deviation of the obtained silicon nitride ceramic substrate material may be ±0.04mm using a micrometer. It was measured that the flatness of the obtained silicon nitride ceramic substrate material may be 0-0.002mm / mm using a profiler. It was measured that the surface roughness of the obtained silicon nitride ceramic substrate material may be 0.3-0.8μm using a profiler. In the present invention, if the obtained silicon nitride ceramic substrate material simultaneously satisfies the above parameters, it can be considered as a qualified product. The pass rate of the obtained silicon nitride ceramic substrate is 60% or more, preferably the pass rate is 70% or more, more preferably the pass rate is 80% or more, and most preferably the pass rate is 90% or more.
[0036] The present invention will be described in detail below with further examples. Similarly, the following examples are only used to further explain the present invention, and should not be understood as limiting the scope of protection of the present invention. Any essential improvements and adjustments made by those skilled in the art based on the above content of the present invention are all within the scope of protection of the present invention. The following exemplary process parameters are also examples of suitable ranges, that is, those skilled in the art can make selections within suitable ranges based on the description in this specification, and the present invention is not limited to the following exemplary specific values.
[0037] Example of silicon nitride ceramic substrate preparation: First, raw powder (silicon nitride powder and / or silica fume), sintering aid (Y2O3 and MgO), dispersant, defoamer, binder, plasticizer, and anhydrous ethanol were mixed in a sealed container under a protective atmosphere (e.g., N2 atmosphere, pressure 0.1MPa) by ball mill mixing (30-100 rpm, 6-24 hours), and further vacuum degassing (-0.1-10 kPa, 6-24 hours) to produce a non-aggregated, non-bubble mixed slurry. Then, tape casting was performed in a N2 atmosphere (0.1-0.2 MPa), and dried in a flowing heat N2 atmosphere (temperature range 40-85°C, atmospheric pressure 0.1-0.2 MPa, flow rate 10-1000 liters / min), to produce a cast film fabric with a uniform thickness and no bubbles on the surface. Finally, the cut cast film substrate (substrate substrate) was subjected to cold isostatic compression shaping pretreatment (40-200 MPa, 2-10 min) to obtain a silicon nitride ceramic substrate substrate.
[0038] Example 1 Firstly, a silicon nitride ceramic substrate with a thickness of 0.4 mm was prepared by adopting processes such as wet mix, vacuum degassing, and tape casting molding. A thin layer of boron nitride slurry was coated on the substrate surface using a screen printing process, and after the slurry was dried, it was divided into samples with the dimensions of 88 mm x 73 mm. 20 samples with the same specifications were stacked in a high-purity boron nitride crucible with an internal space of 100 mm x 100 mm x 30 mm.
[0039] Next, the boron nitride crucibles with the silicon nitride ceramic substrate inside were evenly placed on a sintering tool (also called a graphite furnace tool) made of a high-purity graphite multi-layer shed structure, which was then placed in a pressure sintering furnace and heat-treated according to the following process sequence. (1) Vacuuming for 15 minutes. The vacuum level was increased to 65-75 kPa, followed by 15 minutes of vacuuming until the vacuum level reached 15-25 kPa. The vacuum level was then increased to 1-2 Pa. (2) The vacuum system was closed and N2 (containing 5% H2) gas was slowly injected up to 0.15 MPa. (3) In an atmosphere of 0.15 MPa N2 (containing 5% H2), the temperature was raised to 700°C at a rate of 5°C / min, and then the specimen was left for 2 hours. Debinding Pretreatment was performed. (4) The sample was heated to 1700°C at a rate of 5°C / min under a 0.15 MPa N2 atmosphere, and then subjected to low-temperature heat treatment for 1 hour. (5) The atmospheric pressure inside the sintering furnace was increased to 8 MPa using a N2 atmosphere, and the temperature was raised to 1920°C at a rate of 4°C / min under the protection of an 8 MPa N2 atmosphere, and then high-temperature sintering was performed for 5 hours. (6) Cool in the furnace to room temperature.
[0040] Referring to FIG. 1 , the silicon nitride ceramic substrate produced in this Example 1 had a thermal conductivity of 93 W / (m K), a breakdown electric field strength of 42 KV / mm, a substrate size of 70 mm × 58 mm, a thickness of 0.32±0.02 mm, a flatness of 0.03 mm, and a surface roughness of 0.4 μm. There was no adhesion phenomenon between the substrates and they were easy to peel off. There was no obvious difference between different substrates in the same crucible, and there was no obvious difference between different substrates in different crucibles in the same furnace.
[0041] Examples 2 to 5 Fabric size, characteristics of boron nitride powder for substrate fabric isolation (impurity content, average particle size, coating amount), substrate fabric deposition quantity, vacuum drawing process, graphite grill structure type, Debinding Specific parameters of the process, sintering process, etc. are shown in Table 1 (FIG. 8) and Table 2 (FIG. 9). The process steps refer to Example 1. The material properties of the fabricated substrate are shown in Table 3.
[0042] Example 6 Specific process parameters are shown in Table 1 (FIG. 8) and Table 2 (FIG. 9), the process steps are referred to Example 1, and the properties of the fabricated substrate material are shown in Table 3 (FIG. 10). Because the average particle size of the boron nitride powder used was relatively small, partial adhesion occurred between the fabricated substrates. The pass rate was lower than that of Example 1.
[0043] Example 7 Specific process parameters are shown in Table 1 (FIG. 8) and Table 2 (FIG. 9), the process steps are referred to Example 1, and the properties of the fabricated substrate material are shown in Table 3 (FIG. 10). Because the amount of boron nitride powder used was relatively small, partial adhesion phenomenon occurred between the fabricated substrates. The pass rate was lower than that of Example 1.
[0044] Example 8 Specific process parameters are shown in Table 1 (FIG. 8) and Table 2 (FIG. 9), the process is referred to in Example 1, and the properties of the fabricated substrate material are shown in Table 3 (FIG. 10). A two-stage controlled vacuuming measure is adopted (first, vacuuming for 20 minutes to achieve a vacuum degree of 20-30 kPa, then vacuuming for 15 minutes to achieve a vacuum degree of 1-2 Pa), and a measure is taken to control the vacuuming speed in stages. Although a means for controlling the vacuuming speed in stages was adopted, the vacuuming process was merely divided into two stages, and the vacuuming speed was still fast and the vacuum suction force was still large. As a result, the boron nitride powder between the substrates was partially displaced or pulled out, and the complete isolation between the substrates could not be fully guaranteed, and partial adhesion occurred between the substrates fabricated. The pass rate was lower than that of Example 1.
[0045] Example 9 Specific process parameters are shown in Table 1 (FIG. 8) and Table 2 (FIG. 9). The process steps refer to Example 1, and the properties of the fabricated substrate material are shown in Table 3 (FIG. 10). Debinding Since the process was not adopted (low-pressure nitrogen atmosphere, i.e., 0.05 MPa N2 atmosphere was adopted), the thermal conductivity and breakdown field strength of the material decreased, and microcracks occurred in some samples. The pass rate was lower than that of Example 1.
[0046] Example 10 Specific process parameters are shown in Table 1 (FIG. 8) and Table 2 (FIG. 9). The process steps refer to Example 1, and the properties of the fabricated substrate material are shown in Table 3 (FIG. 10). DebindingSince no process was adopted (slightly positive nitrogen atmosphere, i.e., 0.15 MPa N2 atmosphere), the thermal conductivity and breakdown electric field strength of the material were reduced.
[0047] Example 11 Specific process parameters are shown in Table 1 (FIG. 8) and Table 2 (FIG. 9), the process steps are referred to Example 1, and the properties of the prepared substrate material are shown in Table 3 (FIG. 10). Because the multi-layer grill structure kiln fixture (which plays the dual role of setter board and temperature control) was not made of high heat capacity graphite material, there was a certain temperature difference between different positions inside the hearth of the sintering furnace, and the consistency of the material performance and surface mass (substrate size, flatness, surface roughness, etc.) of the final prepared substrate was relatively low, and the pass rate was lower than that of Example 1.
[0048] Comparative Example 1 Specific process parameters are shown in Table 1 (FIG. 8) and Table 2 (FIG. 9), the process steps are referred to in Example 1, and the properties of the fabricated substrate material are shown in Table 3 (FIG. 10). Because the O content and metal impurity ion content of the employed boron nitride powder were too high, the thermal conductivity and breakdown field strength of the fabricated substrate were obviously reduced, and slight adhesion phenomenon occurred between the substrates.
[0049] Comparative Example 2 The specific process parameters are shown in Table 1 (FIG. 8) and Table 2 (FIG. 9), the process steps refer to Example 1, and the properties of the fabricated substrate material are shown in Table 3 (FIG. 10). Because the C content of the boron nitride powder used is too high, the breakdown field strength of the fabricated substrate is obviously reduced.
[0050] Comparative Example 3 The specific process parameters are shown in Table 1 (FIG. 8) and Table 2 (FIG. 9), the process steps refer to Example 1, and the properties of the fabricated substrate material are shown in Table 3 (FIG. 10). Because the average particle size of the employed boron nitride powder is too large, the flatness of the fabricated substrate is reduced and the surface roughness is obviously increased.
[0051] Comparative Example 4 Specific process parameters are shown in Table 1 (FIG. 8) and Table 2 (FIG. 9), the process steps refer to Example 1, and the properties of the prepared substrate material are shown in Table 3 (FIG. 10). The amount of boron nitride powder used is too large, which inhibits the high temperature shrinkage of the substrate to a certain extent, and the size of the prepared substrate is relatively large, the flatness is reduced, and the surface roughness is obviously increased.
[0052] Comparative Example 5 Specific process parameters are shown in Table 1 (FIG. 8) and Table 2 (FIG. 9), the process steps are referred to in Example 1, and the properties of the fabricated substrate material are shown in Table 3 (FIG. 10). Since a stepwise and slow vacuuming measure (without controlling the vacuum valve opening, directly vacuuming for 30 minutes to reach a vacuum of 1-2 Pa) was not adopted, and the vacuum valve opening (100% full open state) and stepwise vacuuming were not controlled, the vacuum suction force was too large, and the boron nitride powder between the substrates was obviously displaced and even pulled out, so that sufficient isolation between the substrates could not be guaranteed, and serious adhesion phenomenon occurred between the substrates fabricated.
[0053] Comparative Example 6 Specific process parameters are shown in Table 1 (FIG. 8) and Table 2 (FIG. 9), the process procedure is referred to Example 1, and the properties of the fabricated substrate material are shown in Table 3 (FIG. 10). Since the high-pressure nitrogen atmosphere sintering process of 0.5-10 MPa was not adopted (normal pressure nitrogen atmosphere, i.e., N2 atmosphere of 0.1 MPa was adopted), the thermal conductivity and breakdown field strength of the fabricated substrate material were obviously reduced, the surface roughness of the substrate was obviously increased, and the pass rate of the product was reduced.
[0054] Comparative Example 7 Specific process parameters are shown in Table 1 (FIG. 8) and Table 2 (FIG. 9), the process steps are referred to in Example 1, and the properties of the fabricated substrate material are shown in Table 3 (FIG. 10). Because a high-pressure nitrogen atmosphere sintering process of 0.5 to 10 MPa was not adopted (a N2 atmosphere of 0.3 MPa was adopted), the thermal conductivity and breakdown field strength of the fabricated substrate material decreased, the surface roughness of the substrate increased, and the pass rate of the product decreased.
Claims
1. (1) stacking silicon nitride ceramic substrate blanks in a boron nitride crucible, and coating a layer of boron nitride powder between adjacent silicon nitride ceramic substrate blanks; (2) a step of debinding at 500-900° C. in a nitrogen or reducing atmosphere after the stepwise evacuation, the stepwise evacuation being at least a two-stage evacuation or at least a three-stage evacuation, in which in the case of two-stage evacuation, parameters of the stepwise evacuation are evacuation for 20-30 minutes, achieving a vacuum of 20-30 kPa, evacuation for 10-20 minutes, and reducing the vacuum to less than 10 Pa, or in the case of three-stage evacuation, parameters of the stepwise evacuation are first evacuation for 10-15 minutes, achieving a vacuum of 60-80 kPa, evacuation for 10-15 minutes, achieving a vacuum of 10-30 kPa, and finally evacuation for 10-15 minutes, and reducing the vacuum to less than 10 Pa; and (3) pressure sintering at 1800-2000°C in a nitrogen atmosphere to achieve batch fabrication of high performance silicon nitride ceramic substrates; In the step (1), The boron nitride powder has an O content of 1% or less, a C content of 0.01% or less, and a metal impurity ion content of 0.02% or less; The average particle size of the boron nitride powder is 1 μm to 5 μm; In the step (3), the pressure of the nitrogen atmosphere is 0.5 to 10 MPa. A batch sintering method for producing high performance silicon nitride ceramic substrates, comprising:
2. In the step (2), The pressure of the nitrogen atmosphere or the reducing atmosphere is 0.05 to 0.2 MPa; 2. The batch sintering method according to claim 1, wherein the reducing atmosphere is a mixed atmosphere of nitrogen / hydrogen with a hydrogen content of 5% or less, and the debinding time is 1-3 hours.
3. The batch sintering method of claim 1, wherein the pressure sintering time in step (3) is 4 to 12 hours.
4. A batch sintering method as described in claim 1, wherein in step (3), multiple boron nitride crucibles are uniformly arranged in a graphite kiln and pressure sintering is performed.
Citation Information
Patent Citations
Silicon nitride substrate and method for manufacturing silicon nitride substrate
CN103781742A
Silicon nitride sintered substrate, silicon nitride sintered substrate sheet, circuit substrate, and production method for silicon nitride sintered substrate
CN108495831A
High-thermal-conductivity silicon nitride ceramic substrate and preparation method thereof
CN109987944A
Method of sintering silicon nitride
JP1984045970A
Method for manufacturing silicon nitride substrate and silicon nitride substrate
JP2011178598A